Implementasi Pembelajaran Tajwid sebagai Sarana Tadabbur Al-Qur'an di SD Negeri III Kalianan Krucil Probolinggo : Strategi, Tantangan, dan Dampaknya terhadap Pemahaman Keislaman Siswa - M. Untung Sudaryanto; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning tajweed in reading the Qur'an is not just an effort to improve the quality of reading, but also as a means to foster a deep understanding of the contents and messages of the Qur'an (tadabbur). This study aims to analyze the implementation of tajweed learning as a means of tadabbur Al-Qur'an in grade 4 of SD Negeri 3 Kalianan Krucil Probolinggo, focusing on the strategies applied, the challenges faced, and the impact on students' Islamic understanding. This study used a qualitative method with a descriptive approach, involving classroom observation, interviews with teachers and students, and analysis of learning documents. The results show that the strategies used include the talaqqi and musyafahah methods, the use of interactive learning media, and the integration of Islamic values in every learning session. However, the main challenges faced are students' limited initial understanding of the laws of tajweed, the lack of technology-based learning facilities, and the varied levels of ability to read the Qur'an among students. Nevertheless, tajweed learning combined with the tadabbur approach proved effective in increasing students' awareness of the meaning of the verses read and fostering a love for the Qur'an. This study recommends improving supporting facilities such as interactive audiovisual media and special training for teachers to optimize teaching methods.